2016
DOI: 10.4103/0972-0707.194026
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the lining material on the repair of the infected dentin in young permanent molars after restoration: A randomized clinical trial

Abstract: Aim:This study evaluated the impact of liner material on the fluorescence, morphological and mineral characteristics of permanent carious dentin after cavity sealing.Methods:Thirty children (11.0 ± 2.7 years old) presenting at least one active deep carious lesion in permanent molars were selected. Fragments of carious dentin were removed from teeth before lining the cavity (baseline samples) with high-viscosity glass ionomer cement (G1) or an inert material (wax - G2). Cavities were restored with composite res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The main objective of caries removal is to maintain the tooth and pulp health for as long as possible, following the principles of preserving healthy dental tissue, maintaining pulp vitality, and avoiding exposure and maintaining healthy margins to promote correct sealing of the restoration [ 13 ]. Conservative procedures are considered successful when pulp vitality is maintained, and no adverse symptoms are reported after treatment [ 2 ]. None of the six reported cases showed clinical signs of pulp alterations after selective caries removal during a 7- to 21-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main objective of caries removal is to maintain the tooth and pulp health for as long as possible, following the principles of preserving healthy dental tissue, maintaining pulp vitality, and avoiding exposure and maintaining healthy margins to promote correct sealing of the restoration [ 13 ]. Conservative procedures are considered successful when pulp vitality is maintained, and no adverse symptoms are reported after treatment [ 2 ]. None of the six reported cases showed clinical signs of pulp alterations after selective caries removal during a 7- to 21-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Dental caries is the most prevalent noncommunicable disease worldwide, generating substantial direct and indirect costs, and is considered a public health problem [ 1 ]. Restorative treatment of deep carious lesions in young permanent molars presents a challenge for dentists, as complete removal of caries can expose the pulp tissue, necessitating more complex treatments, such as an endodontic treatment [ 2 ], or even early tooth loss [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that although the XMT image alignment is algorithm accurate, some dimensional change is inevitable over time that makes perfect alignment impossible. 13 When digital image subtraction is performed, even a shift of one tenth of a voxel results in a clearly visible line in images with enhanced contrast. This should not be confused with the presence of a marginal gap.…”
Section: Discussionmentioning
confidence: 99%
“…With this respect, Kuhn et al 13 provided evidence that dentine reorganisation and mineral changes were not dependent on the lining material and composite resin used to restore the deep carious lesions by step-wise excavation and indirect pulp capping techniques. It was reported that the carious arrestment (95% success rate) might be due to a host-driven process rather than the effects of dental materials.…”
Section: Introductionmentioning
confidence: 99%